Co-composition and de-composition: Biological agency as a compositional tool. Issue 2 (1st October 2020) - Helyer, Nigel
GeneMusiK is an artistic project that puts into play ideas about the capacity of physical morphologies to act as mnemonic systems by using DNA to transcode and remix musical structures. The project suggests that both biological and cultural information can function as both macro- and micro-scale structures arrayed at physical loci to create topologies which function as keys to the mapping of memory.